SUMBERDAYA IKAN CUCUT (HIIJ) YANG TERTANGKAP NELAYAN DI PERAIRAN L AUT JAWA [The shark resource caught by fishermen in Java Sea] - Agustinus Anung Widodo; Mahiswara Mahiswara (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2007)
Many of fishermen including in Java Sea made shark as fishing target species. Shark is sub group Elasmobranchii and group Cartilaginous. Comparing to the other fish species, information on shark in Indonesia is very lack. In order to identify regarding to the biological aspects on this species, a research was carried out in the year of 2003-2004. Data are got through enumerator and observer program. Sampling location is fish landing bases those covered Muara Angke fishing port (Jakarta), Kejawanan fishing port (Cirebon), Juwana fishing port (Pati) and Brondong fishing port. The kind of data covered shark species, size (TL), fecundity, sex ratio and stomach content. Result shows that there are 34 species of shark caught by fishermen in Java sea which is dominated by Carcharhinus dussumieri (24.74 %), C. melanopterus (8.26 %), Sphyrna lewini (7.26 %), C. falciformis (6.43%) and C.sorrah (6.37 %). The size (TL) of each species are C.dussumieri mostly about 80 cm, C.melanopterus mostly has size about 45 cm and 115 cm, Sphyrna lewini mostly about 190 cm, C falciformis mostly about 90 cm and C.sorrah mostly about 120 cm. As well known that shark is a real predator, but favourite food of shark in Java Sea was shrimp. Fecundity of shark in Java Sea generally was low.